Seepage from an arctic shallow marine gas hydrate reservoir is insensitive to momentary ocean warming - Wei-Li Hong (Nature Portfolio, 2017)
The degree to which warming bottom waters will destabilize shallow gas hydrate reservoirs in the Arctic remains unclear. Here, Honget al. observe and model porewater profiles from a gas-hydrate-bearing system south of Spitsbergen, and conclude episodic emissions are not warming induced.